Karakteristik Perpindahan Panas dan Penurunan Tekanan Pin-Fin Ellips Susunan Segaris Untuk Sistem Pendingin Internal Pada Sudu Turbin Gas - Mardloni, Mukhron (2016)
This study describes a performance prediction of the elliptical pin-fins cooling of gas turbine blade. The main objective of this research is to investigate the heat transfer coefficient (HTC) and friction factor (f) along the cooling passage. The steady RANS with k-epsilon turbulence model was carried out by two-stages investigating: firstly, validation of an existing circular staggered array of pin-fin cooling that has been studied experimentally by other researcher. Five types structured mesh from coarse (Δy+ = 25.15) to fine (Δy+ = 1.22) were optimised for mesh refinement study. Secondly, further investigation of the elliptical pin-fin cooling with in-line orientation was simulated by adopting the same scenario of mesh generation based on the optimum result from validation stage. Simulations were performed by keeping the same initials and boundary conditions as the experiment, and varying Reynolds number from 9000 to 36000. The result shows that validation can be considered acceptable by developing mesh up to 1.6 million elements with fine resolution (Δy+ = 1.22). CFD predicted HTC and pressure loss are in good agreement with available experimental data, although over-prediction data is found after the second pin-fin row for HTC simulation. Investigation of two different surfaces of pin-fin cooling (G2A and G2B) indicates that the HTC of pin-fin G2B is higher than the HTC of pin-fin G2A as the effect of different turbulence around the pinfin cooling. The HTC of pin-fins surface increases moderately along the cooling passage due to the increase of flow turbulence that caused by contraction channel and increasing Reynolds number. On the contrary, the friction factor decreases gradually along the channel.